The Emergence and Development of Materialistic Philosophy in India: A Study - Dikshit, Awadhesh Kumar; Singh, Barun Kumar (Journal of Innovation in Education and Social Research, 2024)
Materialistic philosophy, known as Charvaka or Lokayata, holds a significant yet often underrepresented place in the history of Indian philosophy. This paper explores the origins, development, and impact of materialistic philosophy in India. Through an examination of ancient texts, scholarly interpretations, and historical contexts, this study aims to provide a comprehensive understanding of the Charvaka school and its contributions to Indian philosophical thought.